Estado del conocimiento de la seguridad vial en el Departamento De Boyacá - González Camargo, Angie Tatiana (Universidad Antonio Nariño, 2023)
Road safety has become a problem for the department of Boyacá, due to the low capacity of roads with the increase of vehicles, which has caused an increase in traffic accidents in recent years, where the road actors most affected by these events are pedestrians and motorcyclists, this is how the purpose of this research is born, which is to determine and analyze the state of road safety according to a literature review on this topic. For this study a non-experimental methodology was established, which includes a review and analysis of databases, statistics and research articles, where the causes that influence the frequency of these incidents were identified, as well as the level of performance of road actors according to the National Road Safety Agency, where the misuse of protective elements, performing activities that distract the attention on the road, exceeding the speed limit, failure to comply with traffic rules and performing activities that distract the attention on the road, exceeding the speed limit, According to the results obtained, it is concluded that it is necessary to continue researching on this topic and measures aimed at reducing the most frequent patterns and improving the behavior of road actors when traveling on the roads are presented as a contribution through an informative brochure.